Nonprofit Leader Perceptions of Operating Reserves and Their Substitutes. Issue 4 (4th April 2016) - Sloan, Margaret F.; Charles, Cleopatra; Kim, Mirae
Abstract : This exploratory study has three objectives: (1) to understand the various ways academics, consultants, and practitioners conceptualize operating reserves; (2) to explore differences among academic findings, consultant recommendations, and nonprofit leader perceptions of operating reserves; and (3) to identify how practitioners operationalize operating reserves within their organizations. Using intensive interviews with nonprofit executives, we find that the operating reserve ratio (ORR) commonly used in the nonprofit literature does not accurately indicate whether an organization holds an operating reserve according to nonprofit leaders. In addition, results indicate that experienced nonprofit leaders perceive a variety of other fund types including endowment and investment savings as well as ability to borrow, other assets, sister foundations, and donor networks as legitimate substitutes for a reserve.